Staff strategies for dealing with care situations at an emergency department. Issue 4 (21st December 2019) - Frank, Catharina; Elmqvist, Carina
Abstract : Introduction: Overcrowding is a common international problem at Emergency Departments often due to those patients get recommendations or referrals from other health professionals to seek care at the emergency department. Crowding brings with it an amount of adverse consequences for both patients and staff, and knowledge about staff's strategies of dealing with this caring situation is limited. Aim: The aim of the present study was thus to describe staffs' strategies to deal with the caring situations at an emergency department. Method: Secondary analysis has been made of 18 qualitative interviews grounded in a lifeworld perspective. The interviews were analysed by qualitative content analysis. Findings: The results showed that the staff at the ED worked in twofold directions using both proactive and reactive strategies in order to deal with the care situation when caring for patients at ED. The proactive strategy is optimising conditions, controlling patient flow and being boundary. The reactive strategy is about customising the conversation and holding an open approach. Conclusion: In conclusion, the proactive strategy is to make what you decided for unseen circumstances. The reactive strategy is then about less anticipation of the encounter, waiting for the patient to act and react to it. Implication: The result can have implications with respect to developing and improving care at crowded Emergency departments. Knowledge about strategies creates a fundament for developing visible sustainable structure for patient flow in making work patient safety for patients, staff and organisation.